A ascensão de aspectos do common law no sistema processual civil brasileiro: uma crítica à aplicação da jurisprudência e à doutrina dos precedentes judiciais - Cavarzani, Vinicius [UNESP] (2015)
This work aims to criticize the importation and incorporation of concepts and institutes which were developed in the common law tradition to the Brazilian legal system. To do so, the study was divided into four parts that, though different, are interrelated. At first it was established the conceptual and methodological assumptions that guided all the work, among which stand out the post-positivism of Friedrich Müller and the supremacy of the Constitution. In a second moment, the study conducted analysis of the two major legal traditions of the Western world, namely, the common law and the civil law. From the collation of both legal traditions, Brazilian legal system was analyzed, framing it in the Roman-Germanic legal tradition. In a third moment, the study focused on the main characteristics inherent to common law, especially its distinctive elements. In a fourth moment, it was proved an existing conceptual confusion in the Brazilian legal system regarding the mistaken use of foreign legal concepts. From these four points, a critique of how the judicial precedent idea has been used by Brazilian law was made